Perlindungan Hukum Terhadap Justice Collaborator Tindak Pidana Korupsi Di Indonesia Dan Jerman - Ariyanti, Dwi Oktafia; Muhammad Ramadhan (Program Studi Hukum Universitas Nusa Putra, 2023)
A justice collaborator can be threatened because of his testimony to uncover major crimes such as criminal acts of corruption, so a regulation is needed that specifically, clearly and definitely provides protection for a justice collaborator. This research was carried out using a normative juridical research type, which is an approach based on the main legal material by examining theories, concepts, legal principles and statutory regulations related to this research. The approaches taken are the statutory approach, the analytical approach and the comparative approach. Provisions regarding the protection of justice collaborators are contained in various regulations, but there are no regulations that specifically, clearly and firmly regulate the protection and procedural arrangements for determining a justice collaborator. The handling of protection for justice collaborators in Germany is handled by the Witness Protection Unit Office